1996
DOI: 10.1097/00007890-199609270-00008
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Thrombosis and Stenosis in Pediatric Liver Transplantation1

Abstract: The aim of this study was to determine the outcome of venous conduits used in living donor liver transplantation (LDLT). We analyzed the portal vein complications in 66 LDLT recipients and 48 cadaveric reduced-size liver transplant (RLT) recipients performed from November 1989 through January 1995. Three different venous conduits were utilized in the LDLT recipients: Group 1, reconstructed vein from the living donor, n=18; Group 2, cadaveric cryopreserved iliac vein, n=37; and Group 3, cadaveric cryopreserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
118
1
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 17 publications
0
118
1
7
Order By: Relevance
“…1 It can usually be managed intraoperatively by one of a variety of reconstructive techniques. [1][2][3][4] The choices include thromboendovenectomy, venous jump grafts, and use of collateral veins to revascularize the liver with portal venous blood. In a small proportion of patients, occlusion of the portal, splenic, and superior mesenteric veins may make portal inflow to the graft impossible.…”
mentioning
confidence: 99%
“…1 It can usually be managed intraoperatively by one of a variety of reconstructive techniques. [1][2][3][4] The choices include thromboendovenectomy, venous jump grafts, and use of collateral veins to revascularize the liver with portal venous blood. In a small proportion of patients, occlusion of the portal, splenic, and superior mesenteric veins may make portal inflow to the graft impossible.…”
mentioning
confidence: 99%
“…PVT in pediatric LDLT can have multiple etiologies. Some of them are Porto-caval shunts, atretic portal vein, large for size graft, difficult abdominal closure, low perfusion states in the post-operative period and hypercoagulable states [7]. Post LT, PVT is associated with higher mortality rates.…”
Section: Resultsmentioning
confidence: 99%
“…Many reports have indicated that there is a high incidence of portal vein complications when venous conduits are used to reconstruct the donor and recipient portal veins. 4,5 The reported incidence of early portal vein thrombosis varies between 0% and 30%, depending on the series selected. [6][7][8][9] Several factors have been implicated, including the portal vein size, type of graft used, and graft positional factors.…”
Section: Discussionmentioning
confidence: 99%
“…Late portal and hepatic vein stenoses are commonly present with varied clinical signs and syndromes, including new-onset ascites, variceal bleeding, splenomegaly, increases in liver enzymes, lower extremity edema, and renal insufficiency. 4 The diagnosis of portal vein stenosis or thrombosis can be suggested by abdominal ultrasound findings. Confirmation and common therapeutic interventions for all venous stenoses are done by invasive angiography; thus, interventional radiology is essential.…”
Section: Discussionmentioning
confidence: 99%